2022
DOI: 10.32434/0321-4095-2022-140-1-39-46
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and study of ferri-diopside ceramic pigments

Abstract: The article reports the mineralogical composition, structural features and changes in color parameters of iron-containing diopside pigments. The source of SiO2 in these pigments was SiO2nH2O with a particle size in the range of 2–7 m, which is much more reactive than conventionally used quartz sand. A series of ceramic pigments on the basis of stoichiometric diopside in the system CaO–Fe2O3–MgO–SiO2 was synthesized via solid-state high temperature sintering at 1000, 1100 and 12000C. The resulting ceramic pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It leads to an increase in the activity and a decrease in the work function of electrons from the iron surface. Other reports also indicated that introducing Eu 2 O 3 [50] or CeO 2 [50][51][52][53][54] develops the surface area and increases the porosity of the reduced iron catalyst.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…It leads to an increase in the activity and a decrease in the work function of electrons from the iron surface. Other reports also indicated that introducing Eu 2 O 3 [50] or CeO 2 [50][51][52][53][54] develops the surface area and increases the porosity of the reduced iron catalyst.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…Therefore, stable ceramic pigments of various colours can be obtained, particularly based on the diopside mineral CaO•MgO•2SiO 2 . During firing, the processes of isomorphic substitution, as a rule, of Mg 21 by Co 21 , Ni 21 , Mn 21 and Fe 21 ions occur in the diopside structure, and it determines the formation of a particular colour (Maslennikova and Pisch, 2009;Dimitrov et al, 2017;Dimitrov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of NiO into the composition of diopside pigments in the amount of 0.3-0.8 mol instead of MgO leads to the formation of a light green colour of varying intensity. When MgO is replaced by MnO or FeO in the diopside, brown pigments are predominantly synthesised (Maslennikova and Pisch, 2009;Dimitrov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%